The Influence of Exploration on External Corporate Venturing Activity - Titus, Varkey; House, Jenny M.; Covin, Jeffrey G. (Journal of Management, 2017)
We utilize the exploration/exploitation framework to examine how a firm’s engagement in exploration influences its portfolio of external corporate venturing (ECV) activities. Three forms of equity-based ECV are considered: corporate venture capital investments, joint ventures, and acquisitions. The organizational learning literature is used to investigate how a firm’s engagement in exploration influences its usage of acquisitions relative to its overall portfolio of ECV activities. The investing firm’s industry technological dynamism is posited as a moderator of the relationship between exploration and the relative usage of acquisitions. Utilizing a sample of 1,326 firm-year observations between 1996 and 2008, we find that exploration is positively related to the relative usage of acquisitions, though this relationship is moderated by the investing firm’s industry technological dynamism.